Otredad dentro del capitalismo: Etnografía móvil con una migrante en una tienda de lujo de Londres en 2023 - Martucelli García, Daniela (2024)
This study provides a detailed analysis of the experience of a Latina migrant in the city of London. The complexities of her integration into the British capital are explored through mobile ethnography. The case of the young Peruvian girl reveals how urban mobility between the neighbourhoods of Elephant Castle and Kensington translates into a transition between social and economic worlds that influence her identity and consumption habits. Thus, the study examines the racialization she experiences and her perception of economic differences from her work at the luxury department store Harrods. These factors result in her feeling external to the capitalist system, even while being economically and legally integrated into it. The findings contribute to understanding the social, economic, and cultural dynamics affecting the lives of migrants in urban contexts.